Determination of soil strength characteristics performing the plate bearing test - Pantelidis, Lysandros (My University, 2005)
In the international literature there is often confusion between the terms Modulus of Elasticity EYoung and Modulus of Deformation EDef for homogenous, isotropic masses, which, sometimes, plainly referred as Modulus E, without any further explanation. In this paper a distinction between the EYoung and the EDef is being done and the interest is concentrated in the Plate Bearing Test, which is commonly used in highway earthworks. Moreover, a soil classification diagram is given, in which the soils are classified by their shear strength parameters and their behavior, as totally elastic or elastoplastic, under specific loading applied by rigid circular plate. Finally, a method for the estimation of the soil parameters is proposed, using only the in-situ Plate Bearing Test. The study and the documentation were supported by a presentation of theoretical examples, based on the Finite Element Method.
Keywords: Soil strength; Plate bearing test